Integration Host Factor Modulates the Expression and Function of T6SS2 in Vibrio fluvialis - Pan, Jingjing; Zhao, Meng; Huang, Yuanming; Li, Jing; Liu, Xiaoshu; Ren, Zhihong; Kan, Biao; Liang, Weili (Frontiers in Microbiology, 2018)
Vibrio ﬂuvialis, an emerging foodborne pathogen of increasing public health concern, contains two distinct gene clusters encoding type VI secretion system (T6SS), the most newly discovered secretion pathway in Gram-negative bacteria. Previously we have shown that one of the two T6SS clusters, namely VflT6SS2, is active and associates with anti-bacterial activity. However, how its activity is regulated is not completely understood. Here, we report that the global regulator integration host factor (IHF) positively modulates the expression and thus the function of VflT6SS2 through co-regulating its major cluster and tssD2-tssI2 (also known as hcp-vgrG) orphan cluster. Specifically, reporter gene activity assay showed that IHF transactivates the major and orphan clusters of VflT6SS2, while deletion of eitherihfA or ihfB, the genes encoding the IHF subunits, decreased their promoter activities and mRNA levels of tssB2, vasH and tssM2 for the selected major cluster genes and tssD2 and tssI2 for the selected orphan cluster genes. Subsequently, the direct bindings of IHF to the promoter regions of the major and orphan clusters were confirmed by electrophoretic mobility shift assays (EMSAs). Site-directed mutagenesis combined with reporter gene activity assay or EMSA pinpointed the exact binding sites of IHF in the major and orphan cluster promoters, with two sites in the major cluster promoter, consisting with its two observed shifted bands in EMSA assay. Functional studies showed that the expression and secretion of hemolysin-coregulated protein (Hcp) and the VﬂT6SS2-mediated antibacterial virulence were severely abrogated in the deletion mutants of ∆ihfA and ∆ihfB, but restored when their trans-complemented plasmids were introduced, suggesting that IHF mostly contributes to environmental survival of V. ﬂuvialis by directly binding and modulating the transactivity and function of VﬂT6SS2.